Penyusunan Pola Perjalanan Wisata di Desa Wisata Pagerharjo, Kecamatan Samigaluh, Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Endang Komesty; Cucu Kurniati; Nur Komariah; Ayu Nurwitasari (Politeknik Pariwisata NHI Bandung, 2021)
The Covid-19 pandemic has destroyed almost all of the world's tourism activities. But behind that, the pandemic brings opportunities to change the tourism industry, such as creating new trends for people to travel such as nature tourism, staycations, and road trips because they are considered safer. One of the destinations that tourists choose to unwind is Borobudur. The tourist village located in the buffer zone of the Borobudur destination is Pagerharjo Village which has 10 hamlets. However, until now there has been no pattern of travel involving all hamlets in the Pagerharjo Village area. This study aims to produce recommendations for several travel patterns based on an inventory of tourist attractions, facilities and infrastructure, accessibility, distance and travel time in Pagerharjo Village. This study uses descriptive qualitative research methods using in Ibrahim (2015). The data obtained were based on interviews with the Borobudur Authority Agency (BOB), the Village Head of Pagerharjo Village and Kompepar of Pagerharjo Village. So that the resulting recommendations will make it easier for tourists to travel in Pagerharjo Village.